2018
DOI: 10.1111/cmi.12853
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ca++uptake by erythrocytes infected with malaria parasites: Evidence for exported proteins and novel inhibitors

Abstract: Malaria parasites export many proteins into their host erythrocytes and increase membrane permeability to diverse solutes. Although most solutes use a broad-selectivity channel known as the plasmodial surface anion channel, increased Ca uptake is mediated by a distinct, poorly characterised mechanism that appears to be essential for the intracellular parasite. Here, we examined infected cell Ca uptake with a kinetic fluorescence assay and the virulent human pathogen, Plasmodium falciparum. Cell surface labelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
(104 reference statements)
1
13
0
Order By: Relevance
“…In addition, P. falciparum can activate Ca 2+ influx of the RBC host. Early 45 Ca 2+ flux studies indicated that net Ca 2+ entry into infected RBCs was approximately 20 times faster than into uninfected cells [79], which agrees well with the reported elevated Ca 2+ conductance of patched membranes from infected RBCs [80]. This increased accumulation rate could not be explained by inhibition of the Ca 2+ pump, a cell membrane ATPase that keeps the Ca 2+ of uninfected RBCs very low.…”
Section: Purinergic Signalingsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, P. falciparum can activate Ca 2+ influx of the RBC host. Early 45 Ca 2+ flux studies indicated that net Ca 2+ entry into infected RBCs was approximately 20 times faster than into uninfected cells [79], which agrees well with the reported elevated Ca 2+ conductance of patched membranes from infected RBCs [80]. This increased accumulation rate could not be explained by inhibition of the Ca 2+ pump, a cell membrane ATPase that keeps the Ca 2+ of uninfected RBCs very low.…”
Section: Purinergic Signalingsupporting
confidence: 80%
“…I.e., when RBCs were infected with a parasite knocked down for PTEX (a translocon for export of parasite proteins into the host cell), Ca 2+ uptake was highly reduced. Moreover, a cell-based high-throughput screen for specific Ca 2+ transport inhibitors confirmed a protein-mediated uptake mechanism on infected cells distinct from the low capacity Ca 2+ carrier of RBCs [79] (Figure 1).…”
Section: Purinergic Signalingmentioning
confidence: 99%
“…The membrane-permeable dye crosses into the cell, where it is cleaved by esterases and retained inside the cell; the fluorescence intensity is proportional to the calcium concentration [ 68 ]. Cal520-AM and other calcium-sensitive AM dyes have previously been applied to uRBCs and iRBCs [ 67 , 69 ], supporting the notion that the RBC cytoplasm contains sufficient esterase activity to ensure this is not a rate-limiting step in fluorescence intensity. We observed significantly higher fluorescence in whole iRBCs compared to uRBCs, equalling approximately a 7.5-fold-change (± 0.9, p < 0.001) ( Fig 3A ).…”
Section: Resultsmentioning
confidence: 91%
“…We next quantified the intracellular calcium content of uRBCs and late-stage (trophozoite/schizont) iRBCs using the calcium-sensitive fluorescent dye Cal520-AM [ 67 ]. The membrane-permeable dye crosses into the cell, where it is cleaved by esterases and retained inside the cell; the fluorescence intensity is proportional to the calcium concentration [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies of incorporation and utilization of host factors have focused on low-molecular-weight compounds such as sugars, lipids, vitamins, and ions [19][20][21][22][23][24][25]. However, in recent decades, there has been accumulating evidence for the import of functional proteins by malariainfected erythrocytes.…”
mentioning
confidence: 99%